2013
DOI: 10.3390/md11010050
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin Enhances Cisplatin-Induced Cytotoxicity via NFκB-Mediated Pathway and Downregulates DNA Repair Gene Expression in Human Hepatoma HepG2 Cells

Abstract: Cisplain, a platinum-containing anticancer drug, has been shown to enhance DNA repair and to inhibit cell apoptosis, leading to drug resistance. Thus, the combination of anticancer drugs with nutritional factors is a potential strategy for improving the efficacy of cisplatin chemotherapy. In this study, we investigated the anti-proliferative effects of a combination of fucoxanthin, the major non-provitamin A carotenoid found in Undaria Pinnatifida, and cisplatin in human hepatoma HepG2 cells. We found that fuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 61 publications
5
39
0
Order By: Relevance
“…In our study, the ratio was increased indicating that exposure to these drugs can activate apoptosis cascade. The result is in line with several previous studies that showed that exposure of cells to 5-FU, CDDP and ET increased the ratio of BAX/BCL2 expression (Liu et al 2013;Sawada et al 2000;Singh et al 2006).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the ratio was increased indicating that exposure to these drugs can activate apoptosis cascade. The result is in line with several previous studies that showed that exposure of cells to 5-FU, CDDP and ET increased the ratio of BAX/BCL2 expression (Liu et al 2013;Sawada et al 2000;Singh et al 2006).…”
Section: Discussionsupporting
confidence: 94%
“…The net result was inhibition of TP-mediated antiapoptosis leading to enhanced cisplatin cytotoxicity. Similar results were reported by another group using human hepatoma HepG2 cells [79]. Liu et al found that treating human hepatoma HepG2 cells with cisplatin alone led to increased TP expression through phosphorylation of ERK, p38 and PI3K/AKT pathways.…”
Section: Targeting Thymidine Phosphorylasesupporting
confidence: 88%
“…The carotenoid fucoxanthin has been reported to inhibit NF-jB in HepG2 cells (Liu et al 2013). Sulphated polysaccharides such as fucoidan are known to possess immunomodulating as well as anti-inflammatory effects (Leiro et al 2007).…”
Section: Effect Of T Ornata and P Pavonia On Liver Nf-jb And Pparc mentioning
confidence: 99%